Congenital peripheral nerve hypoplasia: a report of seven cases. (December 2020) - Tian, Xiaofei; Lam, Wee Leon; Guo, Wen; Chen, Tao; Chen, Shanlin
We report the clinical findings of congenital peripheral nerve hypoplasia in seven patients. All seven children presented with unilateral ulnar or median nerve palsy or both. They were assessed clinically, and nerve diameters were assessed with ultrasonography and compared with the contralateral limb. Nerve conduction studies were performed in five children, and the nerves were explored in the four children who presented with accompanying constriction bands. By ultrasonography, the mean diameter of the ulnar nerve was 63% and 29% when compared with the normal arm and forearm, respectively, and the mean diameter of the median nerve was 63% and 46%. Hypoplasia in the nerve was not confined to constriction points but occurred in the entire upper limb in all seven cases. These patients were followed for an average of 12 months (range 6 to 30). Despite neurolysis and surgical decompression in four patients, none of the nerve palsies had recovered. The clinical findings suggest that this condition cannot be explained by simple mechanical compression, and more extensive pathological changes in the involved upper limb are evident in this rare disease. Level of evidence: IV